Effect of climate change on potential evapotranspiration: a case study on Gharehsoo sub-basin, Iran. (1st January 2012) - Abdolhosseini, Mohammad; Eslamian, Saeid; Mousavi, Sayed-Farhad
Potential evapotranspiration (ET0 ) as an important factor in hydrologic cycle has a key role in integrated watershed management practices. Moreover, study of the lack of precipitation with respect to ET0 is one of the main references in management of extreme events. In this study, Gharehsoo sub-basin as a part of Caspian Sea watershed located in Golestan province at Northern Iran is studied to indicate the impact of climate change on ET0 for future periods in such basin with high flood tendency. The A2 emission scenario, HadCM3 and SDSM downscaling models were applied. The results indicate that the amount of precipitation will increase in December, January, and February and decrease in other months and the amounts of ET0 in all future periods will be significantly lower than its amount in the past. For all future periods, the impact of climate change has appeared by reducing precipitation and ET0 in such a way that the reduction of ET0 is more than the reduction of precipitation. The noticeable point is that this difference beside the trend of monthly variations in precipitation will lead to higher flood tendency which directly make it essential to apply climate change adaptation procedures.